2018
DOI: 10.1051/0004-6361/201731816
|View full text |Cite
|
Sign up to set email alerts
|

Young planets under extreme UV irradiation

Abstract: The K2-33 planetary system hosts one transiting ∼5 R⊕ planet orbiting the young M-type host star. The planet's mass is still unknown, with an estimated upper limit of 5.4 MJ . The extreme youth of the system (<20 Myr) gives the unprecedented opportunity to study the earliest phases of planetary evolution, at a stage when the planet is exposed to an extremely high level of high-energy radiation emitted by the host star. We perform a series of 1D hydrodynamic simulations of the planet's upper atmosphere consider… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 56 publications
1
23
0
Order By: Relevance
“…The influence of the equilibrium temperature on the velocity at the Roche radius is however unclear, possibly because variations in the equilibrium temperature imply simultaneous changes in the atmospheric structure and in the orbital separation, thus in the Roche radius. In Kubyshkina et al (2018), we showed that, keeping planetary mass and radius fixed, the effects of T eq variations on the velocity are negligible for planets with Λ greater than 20, while for planets with lower Λ the velocity may significantly decrease with increasing temperature.…”
Section: Outflow Velocity At the Roche Radius And Maximum Atmosphericmentioning
confidence: 89%
See 3 more Smart Citations
“…The influence of the equilibrium temperature on the velocity at the Roche radius is however unclear, possibly because variations in the equilibrium temperature imply simultaneous changes in the atmospheric structure and in the orbital separation, thus in the Roche radius. In Kubyshkina et al (2018), we showed that, keeping planetary mass and radius fixed, the effects of T eq variations on the velocity are negligible for planets with Λ greater than 20, while for planets with lower Λ the velocity may significantly decrease with increasing temperature.…”
Section: Outflow Velocity At the Roche Radius And Maximum Atmosphericmentioning
confidence: 89%
“…Our hydrodynamic code includes X-ray heating and H + 3 cooling, which are relevant for some of the planets close to our grid boundaries. The addition of X-ray heating provides us also with a further important degree of freedom relevant for young, close-in planets, which are subject to strong blow-off (e.g., Kubyshkina et al 2018). We provide below a detailed description of the modelling scheme.…”
Section: The Hydrodynamical Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…Theoretical evolution models predict that the most significant changes in the bulk and orbital parameters of exoplanets occur in the first few hundred Myr of their evolution (e.g., Adams & Laughlin 2006;Kubyshkina et al 2018a;Raymond et al 2009). Planets orbiting stars in young open clusters are thus particularly valuable tests of these models.…”
Section: Introductionmentioning
confidence: 99%